Factors impact the adherence rate of prophylaxis for deep venous thrombosis in acute ischaemic stroke patients: an analysis of the China National Stroke Registry. (20th May 2015) - Li, Zixiao; Liu, Liping; Wang, Yilong; Zhao, Xingquan; Wang, David Z.; Wang, Chunxue; Li, Hao; Wang, Chunjuan; Qin, Haiqiang; Wang, Xianwei; Wang, Yongjun
Abstract : Objectives: Little is known about the clinical practice of deep venous thrombosis (DVT) prophylaxis in patients with acute ischaemic stroke in China. We examined the factors that impact the adherence rate of DVT prophylaxis in stroke patients from the China National Stroke Registry (CNSR). Methods: Records of 12 173 acute ischaemic stroke patients with follow-up admitted to 132 hospitals in CNSR from September 1, 2007 to August 30, 2008 were reviewed. Data from 4643 patients eligible for DVT prophylaxis were analysed. Generalised estimating equations were used to identify the patient's and hospital's factors that impact the practice of DVT prophylaxis. Results: Among 4643 acute ischaemic stroke patients eligible for DVT prophylaxis, the overall adherence rate of DVT prophylaxis was 59·6%. The median hospital prophylaxis rate was 57·8% (inter quartile range: 33·3(70·2%). Venous thromboembolism was found in 1·6% of patients. Factors associated with increased likelihood of practicing DVT prophylaxis in the multivariable model included history of atrial fibrillation (AF) ( P = 0·04), receiving rehabilitation evaluation ( P < 0·001), receiving care in the East ( P < 0.001) or Central ( P = 0.001) regions compared to west regions of China. Increasing age ( P = 0.014), NIHSS score on admission ( P < 0.001), annual stroke discharges ( P = 0.001), and the hospital size ( P = 0.003) were associated with lower likelihood of DVT prophylaxis. Discussion: The adherence rate of DVT prophylaxis among non-ambulance patients with acute ischaemic stroke was suboptimal in China. It varied among patients by age, stroke severity, and history of AF, and among hospitals by different locations, number of beds and annual stroke discharges.